#### Answer

0

#### Work Step by Step

We are asked to evaluate $x+3y$ for $x=-6$ and $y=2$. We can plug both values into the expression in order to evaluate.
$(-6)+3(2)=-6+3\times2=-6+6=6+(-6)=6-6=0$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

0

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.